(3aj SHjd KbGaI YQHjI PGJjI (B:s (3GdKbGaI GdYQHjI h GdJQGK (B/s - (3YHO GdOGFe ,YHO Gddg s ((3HjQhJ (B:s (3efThQGJ OGQ GdBOGH ,s, 1983)
(3HfGA GdKbGaI GdbhejI GdPGJjI TYGQ jMJd ebGe GdUOGQI aj GdacQ GdYGdej h GdLgO GdOhdj Gdjhe h gPG GdeWdH djS ebUhOG dPGJg aMSH (B- (3SYjG Gdi JCcjO GdghjI GdNGUI dcd GeI h JjjQ ddMhGQ GdNUjH Hjf GdKbGaGJ Hd gh bHd gPG GdeWdH dG ef GLd JMbjb GdJfejI GdEbJUGOjI h GdELJeGYjI GdJj JSYi GdjgG cd GeI aVdG Yf chf GdJfejI GdKbGajI aj GdhbJ faSg GdgOa GdfgGFj dGj JfejIs
Keywords: (3GdKbGaIs; (3GdKbGaI GdYQHjIs; (3GdKbGaI GdbhejIs